Contradictory Findings? The Connection between Structural Factors, Income Transfers and Poverty in OECD Countries - Tiina Mäkinen (Luxembourg Income Study (LIS), 1998)
The purpose of the paper is to find out what kind of impact different structural factors have on the one hand, poverty and, on the other hand, income transfers. These structural factors have been operationalised as changes in economy, employment and demography. The countries under comparison represent different welfare state models. The analysis shows that when we look at the impact of structural factors on poverty, we find out the difference between demographic variables used: the rate of under 15 years old increases poverty, while the rate of persons 65 years and older decreases it. If the dependent variable - instead of poverty - is income transfers, the result is the opposite. This can be explained by the fact that social policy has primarily been pension policy and this has improved especially the situation of old people. In many countries the development of family policy is just beginning and at present poverty is a threat to quite a few society groups such as single parents and families with children.
Keywords: 330; Armut; Einkommensumverteilung; Sozialpolitik; Familienpolitik; Rentenpolitik; OECD-Staaten